Xylan, Xylooligosaccharides, and Aromatic Structures With Antioxidant Activity Released by Xylanase Treatment of Alkaline-Sulfite–Pretreated Sugarcane Bagasse - Silva, Verônica Távilla F.; Ruschoni, Uirajá C. M.; Ferraz, André; Milagres, Adriane M. F. (Frontiers in Bioengineering and Biotechnology, 2022)
Biomass pretreatment decreases cell wall recalcitrance permitting enzymes to access individual lignocellulose components. In a traditional biorefinery, pretreated biomass is breakdown into soluble monosaccharides and residual insoluble lignin. Despite useful products may be generated from monosaccharides and lignin such as fuels and chemicals, economic viability of traditional biorefinery requires additional product diversification. Taking advantage of pretreated biomass, alternative enzymatic processes could help to add new products in the biorefinery portfolio. With this vision, this study highlighted a wide range of new products attainable from alkaline-sulfite pretreated sugarcane bagasse by treatments with endo-xylanase under controlled conditions. The current enzymatic process assisted the extraction of a relatively polymeric glucuronoarabinoxylan fraction with co-solubilization of short xylooligosaccharides and aromatic compounds. Enzymatically produced hydrolysate was fractionated with increasingly ethanol concentrations (up to 90% (v/v)) providing precipitation of polymeric xylan fractions with varied average molar masses, which represented 48% of the originally extracted material. The non-precipitate fraction was adsorbed onto 4% (w/v) activated charcoal and subsequent elution with an ethanol gradient from 10% to 70% (v/v) providing new xilooligosaccharides and aromatic fractions. Most of the xylooligosaccharides were washed out in 10% to 30% ethanol. DP2 and DP3 structures predominated in the 10%-ethanol fraction, while DP5 structures were significantly enriched in the 30%-ethanol fraction. Higher ethanol concentrations desorbed xylooligosaccharides associated with higher amounts of aromatic compounds. Total aromatics, phenolic structures and p-hydroxycinnamates predominated in the fractions desorbed with 60% and 70% ethanol. The antioxidant activity of produced fractions correlated with the phenolic contents of the fractions. Compiled results indicate that a wide variety of products can be prepared from pretreated biomass using xylanase-aided extraction procedures. Beyond polymeric xylan with low lignin contamination, xylooligosaccharides or even lignin-carbohydrate complexes with antioxidant activity can be included in the biorefinery portfolio based on the currently developed fractionation studies.